2012
DOI: 10.1002/adsc.201100831
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine‐Catalyzed [3+2] and [4+3] Annulation Reactions of C,N‐Cyclic Azomethine Imines with Allenoates

Abstract: Phosphine-catalyzed [3+2] and [4+3]annulation reactions of C,N-cyclic azomethine imines with allenoates have been developed to give a variety of pharmaceutically attractive tetrahydroisoquinoline derivatives in moderate to excellent yields. The two distinct reaction pathways, [3+2] and [4+3]cyclization, depend on the nature of the nucleophilic phosphine and the allenoate. Generally, for α-alkylallenoates, the reactions always proceed with [3 +2]cyclization as the major pathway no matter what phosphine was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(26 citation statements)
references
References 81 publications
1
25
0
Order By: Relevance
“…Despite its great efficiency in construction of 5- or 6-membered rings, phosphine-catalyzed preparation of medium-sized rings was elusive until in 2012. Guo, Zhong, Kwon and coworkers described phosphine-catalyzed [3+2] and [4+3] annulation reactions of α-substituted allenoates with C , N -cyclic azomethine imines for the synthesis of a variety of pharmaceutically important tetrahydroisoquinoline derivatives ( Scheme 22 ) [ 60 ]. Interestingly, they found that the nucleophilic phosphine catalyst together with the allenoate substrates had a great influence on the chemoselectivity of the annulation reaction.…”
Section: [4+x] Annulations Of α-Alkyl Allenoates (Or 2-alkyl 23-bmentioning
confidence: 99%
“…Despite its great efficiency in construction of 5- or 6-membered rings, phosphine-catalyzed preparation of medium-sized rings was elusive until in 2012. Guo, Zhong, Kwon and coworkers described phosphine-catalyzed [3+2] and [4+3] annulation reactions of α-substituted allenoates with C , N -cyclic azomethine imines for the synthesis of a variety of pharmaceutically important tetrahydroisoquinoline derivatives ( Scheme 22 ) [ 60 ]. Interestingly, they found that the nucleophilic phosphine catalyst together with the allenoate substrates had a great influence on the chemoselectivity of the annulation reaction.…”
Section: [4+x] Annulations Of α-Alkyl Allenoates (Or 2-alkyl 23-bmentioning
confidence: 99%
“…Such azomethine imines are highly reactive and add both to electron-deficient and to electron-rich dipolarophiles. The [3+2]-cycloaddition reactions of C,N-cyclic azomethine imines with alkynes, 183 ± 185 alkenes, 151, 152, 186 ± 188 allenoates, 153,189,190 carbon disulfide and isothiocyanates, 155,191 thioesters and thioketones 192 and isocyanides 193 …”
Section: Scheme 57mentioning
confidence: 99%
“…In contrast, as a readily available dipole, the application of nitrilimines in the cycloaddition of Baylis–Hillman adducts is very unsatisfactory, and only a few specific examples were described . As our continuing efforts on cycloaddition reactions , herein, we present a diastereodivergent [3 + 2] cycloaddition of Baylis–Hillman adducts and nitrilimines generated in situ to synthesize an array of pyrazoline derivatives under mild conditions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%